Linking sustainable forest management with habitat conservation for the Amur tiger (Panthera tigris altaica) - Han, Xuemei, speaker; Anderson, David, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The critically endangered wild cat, Amur tiger (Panthera tigris altaica), has experienced a serious shrinking of its range and a significant population decline during the past century in Northeastern China and Russian Far East. This study demonstrates a multi-disciplinary approach to conserve the Amur tiger habitat through sustainable forest management. The forests habitat was evaluated from a dynamic perspective. By applying multiple metrological silvicultural methods, innovative habitat mapping based on the remote sensed data, and the computer model, Landscape Management System, a design of sustainable forest management plan was suggested to keep a diversified stand structures is critical to conserve Amur tigers in Northeast China.
Moderator: David Anderson.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses